AN ANALYSIS OF MATERNAL-FETAL ATTACHMENT LEVEL IN PREGNANT WOMEN - Akbaş, Meltem; Akbaş, Turan; Akbaş, Ozan; Akbaş, Ibrahim (LIFE: International Journal of Health and Life-Sciences, 2017)
This study aims to analyse maternal-fetal attachment levels of pregnant women. The population of the descriptive study consists of pregnant women who consulted Non Stress Test Policlinic of a private hospital and the sample consists of 101 pregnant women who participated in the study willingly. Confirmation of the ethics committee, permission of the institutions and verbal informed consent were obtained. The data were collected via “Questionnaire Form” and “Prenatal Attachment Inventory” with face-to-face interviews and were analyzed on IBM SPSS Statistics version 20. Number, percentage, arithmetic average, independent t test and Pearson Correlation Coefficient were used in the analysis. It was found that the average age for pregnant women was 28,20±4,954, average duration of marriage was 4.67±4.157, average number of pregnancy was 1,82±1,07, average number of delivery was 0,73±0,989, average pregnancy week was 35,88±2,380. It was indicated that 69.3% of the pregnant women were 30 years old and younger, 44.6% had education at university level or higher, 64.4% were not working, 74.3% had good financial status, 92.1% had nuclear family, 94.1% had planned their pregnancy, 74.3% did not experience problems during pregnancy, 61.4% were examined 5 times or more during pregnancy. No statistically significant difference was found between average scores for Prenatal Attachment Inventory of pregnant women and their age, education level, work status, financial status, family type, frequency of health checks, problems experienced during pregnancy and planning of the pregnancy (p>0.05). A weak, positive correlation was found between average scores for prenatal attachment inventory of pregnant women and the number of delivery (p<0.05).The data suggest that the attachment level between mother and fetus is strong in pregnancy; however, significant difference was not found between variables related to mother and average scores for prenatal attachment inventory. A weak, positive correlation was found between average scores for prenatal attachment inventory of pregnant women and the number of delivery (p<0.05).